Stress tolerance in auxin heterotrophic and autotrophic tobacco tissue cultures - Illés, Emese; Szabó, Margit; Csiszár, Jolán (Acta Biologica Szegediensis, 2002)
The natures of the stress tolerance of auxin autotrophic and heterotrophic tobacco calli were compared. SO mM NaCI did not inhibit the growth of auxin autotrophic calli and they exhibited a lower level of peroxidase secretion into the media than that of heterotrophic cultures. The ascorbate peroxidase and catalase activities of these lines did not decrease in the presence of stressors. In the second half of the culturing period, the auxin autotrophic tissues expressed a higher GST activity than that of the heterotrophic lines.